Aluminum alloy for an impact-resistant and explosion-proof membrane and method for manufacturing the same

CN122879561APending Publication Date: 2026-10-09JIANGSU ALCHA ALUMINUM CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611243945.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-17
Publication Date
2026-10-09

AI Technical Summary

Technical Problem

[0006]本发明的目的是提供一种抗冲击防爆膜用铝合金及其制备方法,以解决上述技术中现有防爆膜用铝合金强韧匹配性差、抗冲击性能不足、表面平整度与贴合稳定性差、抗疲劳冲击性能弱、工艺适配性差、强塑性能难以兼顾的问题

Benefits of technology

1.本发明通过Fe、Mn、Si的合理配比(Fe/Si=4.0~8.0,Mn/Fe=0.5~0.9),使铸造组织中富铁相以细小弥散的α-Al(Fe,Mn)Si相为主,避免了常规铝合金中粗大针状β-AlFeSi相的形成,该α相在后续热轧和冷轧过程中能够被进一步破碎和细化,显著降低了对铝箔基体的割裂作用,从而在保证强度的同时大幅提升了材料的延伸率和抗冲击韧性;

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122879561A_ABST
    Figure CN122879561A_ABST
Patent Text Reader

Abstract

This invention discloses an aluminum alloy for impact-resistant and explosion-proof films and its preparation method, relating to the field of aluminum alloy metal materials technology. By mass percentage, it comprises the following components: Fe: 0.8–1.2%; Si: 0.10–0.25%; Cu: 0.02–0.08%; Mn: 0.5–0.9%; Mg: 0.05–0.20%; Ti: 0.005–0.03%; B: 0.001–0.008%; RE (mixed rare earth): 0.03–0.10%; the mixed rare earth comprises Ce, La, and Sc, and the mass ratio of the three is Ce:La:Sc = (3–5):(1–2):(0.5–1); individual impurity elements ≤0.03%, total impurity elements ≤0.10%; the balance is Al. This invention, through a reasonable ratio of Fe, Mn, and Si (Fe / Si = 4.0–8.0, Mn / Fe = 0.5–0.9), ensures that the iron-rich phase in the casting structure is dominated by fine and dispersed α-Al(Fe,Mn)Si phase, avoiding the formation of coarse needle-like β-AlFeSi phase in conventional aluminum alloys. This α phase can be further broken and refined during subsequent hot and cold rolling processes, significantly reducing the cutting effect on the aluminum foil matrix, thereby greatly improving the elongation and impact toughness of the material while ensuring strength.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of aluminum alloy metal materials technology, specifically to an aluminum alloy for impact-resistant and explosion-proof films and its preparation method. Background Technology

[0002] Explosion-proof membranes are critical safety components in energy storage devices such as lithium-ion batteries and supercapacitors. When a battery experiences thermal runaway or an abnormal increase in internal pressure, the explosion-proof membrane can precisely rupture and release pressure under a preset pressure, effectively preventing serious safety accidents such as battery fires and explosions. It is the core barrier of the energy storage equipment's security system. As new energy vehicles, large-scale energy storage power stations, and portable energy storage devices rapidly iterate towards high energy density, high-rate charging and discharging, and long-life operating conditions, the comprehensive performance requirements of energy storage battery packs for explosion-proof membranes are becoming increasingly stringent. Not only do they need precise pressure response characteristics, but higher standards are also being set for the impact resistance, ultra-thin thickness uniformity, mechanical stability, and long-term service consistency of the explosion-proof membrane substrate.

[0003] Currently, the mainstream explosion-proof protection system for energy storage batteries adopts a composite structure of "polymer explosion-proof film + ultra-thin aluminum alloy foil". This structure utilizes the rigid support, stress dispersion, and instantaneous impact energy absorption characteristics of the aluminum alloy foil to compensate for the inherent defects of pure polymer explosion-proof films, such as poor rigidity, weak resistance to instantaneous impact, and susceptibility to plastic deformation failure. This significantly improves the overall structural stability and explosion-proof protection limit of the explosion-proof film. Therefore, the strength and toughness matching, uniformity of structure, ultra-thin forming flatness, fatigue impact resistance, and bonding stability of the aluminum alloy foil directly determine the pressure relief accuracy, impact resistance, and long-term service safety of the energy storage battery explosion-proof film.

[0004] The existing aluminum alloys used for explosion-proof films mostly use conventional 3003 and 5052 general-purpose aluminum alloy grades. These materials have significant technical defects: First, the material has poor strength and toughness matching and insufficient impact resistance. Conventional general-purpose aluminum alloys do not have precise element ratio control, and the matrix is ​​too brittle. When exposed to the instantaneous shock wave of battery thermal runaway or high-speed media impact, they are very prone to plastic deformation and local cracking. They cannot continuously provide rigid support for the polymer explosion-proof film, which directly leads to the premature failure of the explosion-proof protection system and poses a great safety hazard. Secondly, the substrate surface smoothness and structural density are poor. The existing aluminum alloy structure has a high content of coarse and brittle phases and many internal micro-defects. After being prepared into ultra-thin foil, the surface roughness is large and the density is poor. During the process of bonding with the polymer adhesive layer of the explosion-proof film, air bubbles are easily left and the bonding is uneven. After long-term service, problems such as delamination, edge lifting and peeling are likely to occur, resulting in the degradation of the waterproof and anti-oxidation performance of the explosion-proof film, and a significant decrease in the consistency of pressure relief response and explosion-proof durability. Third, conventional aluminum alloys have large grains, many internal impurities and micropores, resulting in significant stress concentration under dynamic loads and poor fatigue impact resistance. Under the alternating impact loads generated by frequent charging and discharging of batteries, stress concentration is easily generated, inducing hidden microcracks. After long-term cyclic service, the cracks propagate and cause the foil to fail, which cannot meet the explosion-proof requirements of long-term and high-stability energy storage equipment. Fourth, the existing aluminum alloy manufacturing process is not targeted enough and has not been optimized for the specific needs of lightweight, high flatness, high toughness and high adhesion of explosion-proof film substrate. It generally suffers from technical bottlenecks such as decreased toughness when strength is increased and insufficient plasticity when hardness is increased. It cannot meet the long-term, efficient and stable impact and explosion-proof requirements of explosion-proof film in high-end security scenarios, and it is difficult to adapt to the harsh operating conditions of high-end energy storage battery explosion-proof film.

[0005] Therefore, it is necessary to invent an aluminum alloy for impact-resistant and explosion-proof films and its preparation method to solve the above problems. Summary of the Invention

[0006] The purpose of this invention is to provide an aluminum alloy for impact-resistant and explosion-proof films and its preparation method, so as to solve the problems of poor strength and toughness matching, insufficient impact resistance, poor surface flatness and bonding stability, weak fatigue impact resistance, poor process adaptability, and difficulty in balancing strength and plasticity in the existing aluminum alloys for explosion-proof films.

[0007] To achieve the above objectives, the present invention provides the following technical solution: an aluminum alloy for impact-resistant and explosion-proof films, comprising the following components by mass percentage: Fe: 0.8–1.2%; Si: 0.10–0.25%; Cu: 0.02–0.08%; Mn: 0.5–0.9%; Mg: 0.05–0.20%; Ti: 0.005~0.03%; B: 0.001~0.008%; RE (mixed rare earth elements): 0.03~0.10%; The mixed rare earth comprises Ce, La and Sc, and the mass ratio of the three is Ce:La:Sc=(3~5):(1~2):(0.5~1); the individual impurity element is ≤0.03%, the total impurity element is ≤0.10%; the balance is Al.

[0008] Preferably, the Fe / Si mass ratio is 4.0 to 8.0.

[0009] Preferably, the mass ratio of Mn / Fe is 0.5 to 0.9.

[0010] Preferably, the mass ratio of Ce:La:Sc in the mixed rare earth is 4:1.5:0.8.

[0011] Preferably, it includes the following steps: S1. Batching and smelting: Weigh the raw materials according to the alloy ratio, heat the aluminum ingot to 740-780℃ to melt it, then add the intermediate alloy and pure magnesium ingot, stir and smelt for 30-60 minutes to obtain the alloy melt; S2. Composite refining and purification: The alloy melt obtained in step S1 is heated to 760-800℃, and high-purity argon and refining agent are introduced by rotary jetting to degas and refine the alloy. The refining time is 15-30 minutes. After refining, the melt is allowed to stand for 10-20 minutes and the slag is removed. S3. Online grain refinement and casting: Adjust the temperature of the melt purified in step S2 to 700-730℃, add Al-5Ti-1B grain refiner online, and then perform semi-continuous casting after filtration through a ceramic filter plate. S4. Two-stage homogenization treatment: The ingot obtained in step S3 is subjected to two-stage homogenization treatment. The first stage is held at 420-450℃ for 6-12 hours, and the second stage is held at 530-560℃ for 12-24 hours. S5. Hot rolling: Heat the ingot after homogenization treatment in step S4 to 480-520℃, hold for 2-4 hours and then hot roll it. The final rolling temperature is controlled at 300-350℃. S6. Intermediate annealing: The hot-rolled strip coil obtained in step S5 is subjected to intermediate annealing under a protective atmosphere. The annealing temperature is 350-420℃ and the holding time is 2-6 hours. S7. Cold rolling and graded aging: The strip annealed in step S6 is subjected to multiple passes of gradient rolling, including roughing, intermediate rolling and finishing rolling, with a total cold rolling deformation of 70-95%, to produce aluminum foil with a thickness of 0.05-0.20 mm; after cold rolling, graded aging heat treatment is performed, with the first stage held at 80-120℃ for 2-6 hours and the second stage held at 150-190℃ for 4-12 hours; S8. Low-temperature stress relief annealing: The aged aluminum foil is subjected to low-temperature precision annealing at 280-300℃ to eliminate residual rolling stress; S9. Precision surface modification: After polishing and cleaning, the annealed aluminum foil is subjected to micro-arc oxidation passivation treatment to obtain the finished aluminum alloy foil.

[0012] Preferably, the refining agent in S2 is composed of the following components by mass percentage: NaCl: 40-50%, KCl: 30-40%, Na3AlF6: 10-20%, Na2B4O7: 2-8%.

[0013] Preferably, the purity of the high-purity argon gas in S2 is ≥99.99%, the gas flow rate is 2-5 L / min, and the amount of refining agent added is 0.1-0.3% of the melt mass.

[0014] Preferably, in the two-stage homogenization process of S4, the first stage temperature is 435-445℃ / 8-10 hours, and the second stage temperature is 540-550℃ / 16-20 hours.

[0015] Preferably, during the cold rolling process in S7, when the cumulative deformation reaches 50-70%, an intermediate annealing is performed at a temperature of 250-320°C for 1-3 hours.

[0016] Preferably, in the graded aging heat treatment in S7, the heating rate is 20-50℃ / hour.

[0017] The technical effects and advantages provided by the present invention in the above technical solution are as follows: 1. This invention, through the rational proportion of Fe, Mn, and Si (Fe / Si=4.0~8.0, Mn / Fe=0.5~0.9), makes the iron-rich phase in the casting structure mainly composed of fine and dispersed α-Al(Fe,Mn)Si phase, avoiding the formation of coarse needle-like β-AlFeSi phase in conventional aluminum alloys. This α phase can be further broken and refined during subsequent hot rolling and cold rolling processes, significantly reducing the cutting effect on the aluminum foil matrix, thereby greatly improving the elongation and impact toughness of the material while ensuring strength; 2. This invention uses Ce, La, and Sc ternary composite rare earth elements for microalloying. Ce and La have the dual functions of purifying the melt and modifying the iron-rich phase, which can further refine the particle size of the iron-containing phase. Sc, on the other hand, generates a strong precipitation strengthening effect during aging by forming nanoscale Al3Sc precipitates. At the same time, the addition of Sc can also effectively inhibit the growth of recrystallized grains, so that the foil can maintain a fine grain structure (average grain size ≤25μm) even in the ultra-thin state (0.05~0.20mm). The composite addition of the three rare earth elements produces a synergistic effect of "purification + modification + precipitation strengthening + grain refinement strengthening", which is a comprehensive effect that is difficult to achieve with single rare earth elements or binary rare earth elements. 3. This invention employs a two-stage homogenization process combining low and high temperatures. The first stage (420–450°C) induces a full spheroidization transformation of the iron-rich phase in the alloy, changing it from needle-like or lath-like structures to granular structures. The second stage (530–560°C) allows elements such as Cu, Mg, and Sc to fully dissolve into the aluminum matrix, laying the compositional foundation for subsequent aging precipitation strengthening. Compared to conventional single-stage homogenization, this two-stage process simultaneously achieves both the optimization of the iron-rich phase morphology and the full dissolution of alloying elements, resolving the inherent incompatibility between these two objectives within the same temperature window. 4. This invention employs a graded aging system of "low-temperature pre-aging + high-temperature final aging" after cold rolling. The first low-temperature stage (80-120℃) promotes uniform nucleation in the GP region, forming a high-density fine precipitate precursor. The second high-temperature stage (150-190℃) transforms the GP region into a fine and dispersed equilibrium phase or metastable phase. Compared with single-stage aging, this graded system produces precipitates with smaller size and more uniform distribution, achieving both high strength (tensile strength ≥175MPa) and good plasticity (elongation ≥30%), thus achieving the best match between strength and plasticity. 5. The aluminum alloy foil (thickness 0.05–0.20 mm) prepared by this invention achieves the following comprehensive performance indicators: tensile strength ≥175 MPa, elongation ≥30%, impact toughness ≥4.5 J / cm² (more than 65% higher than that of aluminum materials used in conventional 3003 explosion-proof films), conductivity ≥53% IACS, and average grain size ≤25 μm. In particular, the simultaneous improvement in impact toughness and conductivity solves the technical problem in existing technologies where aluminum materials used in explosion-proof films struggle to simultaneously achieve both "impact resistance safety" and "conductive reliability." Attached Figure Description

[0018] Figure 1 This is a schematic diagram of the process flow for preparing the aluminum alloy for the impact-resistant and explosion-proof film of the present invention. Detailed Implementation

[0019] To enable those skilled in the art to more clearly and completely understand the technical solutions, principles, and beneficial effects of the present invention, the present invention will be further described in detail and completely below with reference to the accompanying drawings and specific embodiments. The following embodiments are merely preferred implementation examples of the present invention, used to explain the technical features of the present invention, and are not intended to limit the scope of protection of the present invention. Equivalent substitutions, improvements, and optimizations made by those skilled in the art without departing from the core concept of the present invention are all within the scope of protection of the present invention.

[0020] The present invention will be further described in detail below with reference to specific embodiments. Each embodiment is only used to explain the present invention and is not intended to limit the scope of protection of the present invention.

[0021] Example 1 This embodiment presents the optimal formulation and process scheme for adapting to the working conditions of explosion-proof films for energy storage batteries. An aluminum alloy for impact-resistant explosion-proof films has the following composition by mass percentage: Fe: 1.0%, Si: 0.18%, Cu: 0.05%, Mn: 0.7%, Mg: 0.12%, Ti: 0.015%, B: 0.004%, mixed rare earth RE: 0.06%, single impurity ≤ 0.03%, total impurities ≤ 0.10%, and the balance is Al; wherein Fe / Si = 5.56, Mn / Fe = 0.7, and mixed rare earth Ce:La:Sc = 4:1.5:0.8.

[0022] The aluminum alloy preparation method of this embodiment includes the following steps: S1. Batching and smelting: The raw materials are precisely proportioned, the aluminum ingots are melted at 760℃, the intermediate alloy and magnesium ingots are added, and the mixture is kept at the temperature and stirred for 45 minutes to obtain a uniform alloy melt; S2. Composite refining and purification: The melt is heated to 780℃, and 99.99% high-purity argon gas is introduced by rotary jetting at a flow rate of 3.5L / min. 0.2% of the melt mass of composite refining agent (NaCl 45%, KCl 35%, Na3AlF 6 15%, Na2B4O 75%) is added. The refining process is carried out for 22 minutes, and the slag is removed after standing for 15 minutes. S3. Online grain refinement and casting: The melt temperature is adjusted to 715℃, Al-5Ti-1B grain refiner is added online, and after multi-stage ceramic filtration, semi-continuous casting is used to obtain ingots; S4. Two-stage homogenization treatment: first stage heat preservation at 440℃ for 9 hours, second stage heat preservation at 545℃ for 18 hours, followed by slow cooling in the furnace; S5. Hot rolling: The ingot is held at 500℃ for 3 hours, then hot rolled at a final rolling temperature of 320℃ to obtain a hot-rolled strip coil; S6. Intermediate annealing: Hold at 400℃ in a protective atmosphere for 4 hours to eliminate hot rolling stress; S7. Gradient cold rolling and graded aging: When the total cold rolling deformation is 85% and the cumulative deformation is 60%, it is inserted into the intermediate annealing at 300℃ for 2 hours and rolled into 0.1mm ultra-thin aluminum foil; the graded aging heating rate is 30℃ / h, the first stage is held at 100℃ for 4 hours and the second stage is held at 170℃ for 8 hours. S8. Low-temperature stress-relieving annealing: Hold at 290℃ for 2.5h, and control the temperature rise and fall to eliminate residual stress; S9. Surface precision modification: Double-sided polishing to Ra≤0.4μm, degreasing, cleaning and drying, 400V micro-arc oxidation treatment for 10min to form a 4μm dense passivation film, and the finished product is obtained.

[0023] Example 2 An aluminum alloy for impact-resistant and explosion-proof membranes has the following composition by mass percentage: Fe: 0.8%, Si: 0.10%, Cu: 0.02%, Mn: 0.5%, Mg: 0.05%, Ti: 0.005%, B: 0.001%, mixed rare earth RE: 0.03%, single impurity ≤0.03%, total impurities ≤0.10%, and the balance being Al; wherein Fe / Si=8.0, Mn / Fe=0.625, and mixed rare earth Ce:La:Sc=3:1:0.5.

[0024] The preparation process parameters and steps in this embodiment are completely consistent with those in Example 1.

[0025] Example 3 An aluminum alloy for impact-resistant and explosion-proof membranes has the following composition by mass percentage: Fe: 1.2%, Si: 0.25%, Cu: 0.08%, Mn: 0.9%, Mg: 0.20%, Ti: 0.03%, B: 0.008%, mixed rare earth RE: 0.10%, single impurity ≤0.03%, total impurities ≤0.10%, and balance Al; wherein Fe / Si=4.8, Mn / Fe=0.75, and mixed rare earth Ce:La:Sc=5:2:1.

[0026] The preparation process parameters and steps in this embodiment are completely consistent with those in Example 1.

[0027] Comparative Example 1 (Traditional 5052 explosion-proof film aluminum alloy) It uses commercially available 5052 aluminum alloy, without precise Fe / Si or Mn / Fe ratio restrictions, and without ternary rare earth composite modification. It is prepared using industry-standard conventional smelting, single annealing, and single-stage aging processes, and does not use the gradient cold rolling, two-stage homogenization, and graded aging core processes of this invention. It is currently the most commonly used substrate solution in the field of energy storage explosion-proof membranes.

[0028] Comparative Example 2 (Single Ce rare earth modification, without element ratio control) Compared to Example 1, only the same total content of single Ce rare earth modification was added, and the Fe / Si and Mn / Fe dual ratio synergistic control design was cancelled. The other alloy basic components and preparation process were completely consistent with Example 1, which was used to verify the superimposed innovative effect of the **dual ratio element synergy + ternary rare earth composite** of the present invention.

[0029] Mechanical properties, dynamic impact resistance, surface flatness, and bonding stability of each embodiment and comparative sample were tested according to GB / T3880-2012 and GB / T14522-2018 standards. The test results are shown in the table below: The comparative test data above clearly show that the comprehensive performance of the products in each embodiment of the present invention is significantly better than that of traditional aluminum alloys and aluminum alloys modified with single rare earth without proportional control. Among them, Example 1 has the best comprehensive performance, with strength, toughness, dynamic impact resistance, surface flatness and bonding stability all reaching the top level in the industry. This fully verifies the creativity and advancement of the present invention's synergistic control of element proportions + ternary rare earth composite modification + exclusive process system.

[0030] Working principle of this invention: Refer to the instruction manual appendix Figure 1When using this invention, firstly, according to the precise alloy mass ratio defined by this invention, high-purity aluminum ingots, pure magnesium ingots, and various intermediate alloys and ternary mixed rare earth raw materials are precisely weighed, and the content of Fe, Si, and Mn elements and the mass ratio of Fe / Si and Mn / Fe are strictly controlled. The content of impurity elements is also strictly controlled. This ensures that the alloy composition is precise and controllable from the raw material end, laying the compositional foundation for the subsequent formation of fine and dispersed α-Al(Fe,Mn)Si strengthening phase and the realization of multi-element rare earth synergistic modification. Secondly, through rotary jet refining, hydrogen and inclusions in the melt are effectively removed, improving melt purity and reducing the internal defect density of the foil. Online grain refinement and casting further refine the as-cast grains, laying the foundation for obtaining a fine and uniform final grain structure. Then, the purified alloy melt is subjected to online grain refinement treatment, Al-5Ti-1B grain refiner is added and it is filtered through multiple ceramic stages. Aluminum alloy ingots with uniform microstructure are prepared by semi-continuous casting process. Subsequently, a two-stage homogenization heat treatment process is adopted. First, the iron-rich brittle phase is spheroidized and modified by low temperature holding to eliminate harmful brittle phases such as needle-like and lath-like phases. Then, the alloy solute elements are fully dissolved by high temperature holding to optimize the microstructure of the ingot and eliminate casting segregation and internal stress. Furthermore, the homogenized ingot is preheated at a constant temperature and then hot rolled in a gradient manner. The final rolling temperature is precisely controlled to obtain a dense hot-rolled strip coil. The hot rolling stress is eliminated by intermediate annealing in a protective atmosphere. After softening the structure, a multi-pass gradient cold rolling process is adopted, combined with mid-section low-temperature annealing to eliminate work hardening, and the substrate is stably rolled into an ultra-thin aluminum foil substrate with a thickness of 0.05 to 0.20 mm. Subsequently, the ultrathin aluminum foil was subjected to graded aging heat treatment. Low-temperature pre-aging promoted the uniform nucleation of precipitate precursors, followed by high-temperature final aging to form fine and dispersed strengthening phases, achieving the optimal match between alloy strength and plasticity. Finally, low-temperature precision annealing completely eliminated residual stresses from rolling and aging. Combined with mechanical polishing, precision cleaning, and micro-arc oxidation passivation surface modification, a high-flatness, high-density, high-impact-resistance, and high-adhesion-stability explosion-proof film-specific aluminum alloy foil was prepared. Finally, residual stress is eliminated by low-temperature stress relief annealing to prevent foil warping and deformation; a dense passivation film is formed on the surface by micro-arc oxidation treatment with precise surface modification, which improves surface smoothness, corrosion resistance and adhesion stability with the explosion-proof film coating.

[0031] It should be noted that, in this document, relational terms such as "first" and "second" are used only to distinguish one entity or operation from another, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Furthermore, the terms "comprising," "including," or any other variations thereof are intended to cover non-exclusive inclusion, such that a process, method, article, or apparatus that comprises a list of elements includes not only those elements but also other elements not expressly listed, or elements inherent to such process, method, article, or apparatus.

[0032] Although embodiments of the invention have been shown and described, it will be understood by those skilled in the art that various changes, modifications, substitutions and alterations can be made to these embodiments without departing from the principles and spirit of the invention, the scope of which is defined by the appended claims and their equivalents.

Claims

1. An aluminum alloy for an impact-resistant and explosion-proof membrane, characterized in that, It consists of the following components by mass percentage: Fe: 0.8–1.2%; Si: 0.10–0.25%; Cu: 0.02–0.08%; Mn: 0.5–0.9%; Mg: 0.05–0.20%; Ti: 0.005~0.03%; B:0.001~0.008%; RE (mixed rare earth elements): 0.03~0.10%; The mixed rare earth comprises Ce, La and Sc, and the mass ratio of the three is Ce:La:Sc=(3~5):(1~2):(0.5~1); the individual impurity element is ≤0.03%, the total impurity element is ≤0.10%; the balance is Al.

2. The aluminum alloy for an impact-resistant and explosion-proof membrane according to claim 1, characterized in that: The Fe / Si mass ratio is 4.0 to 8.

0.

3. The aluminum alloy for an impact-resistant and explosion-proof membrane according to claim 1, characterized in that: The mass ratio of Mn / Fe is 0.5 to 0.

9.

4. The aluminum alloy for an impact-resistant and explosion-proof membrane according to claim 1, characterized in that: The mass ratio of Ce:La:Sc in the mixed rare earth is 4:1.5:0.

8.

5. A method for preparing an aluminum alloy for an impact-resistant and explosion-proof film according to any one of claims 1 to 4, characterized in that, Includes the following steps: S1. Batching and smelting: Weigh the raw materials according to the alloy ratio, heat the aluminum ingot to 740-780℃ to melt it, then add the intermediate alloy and pure magnesium ingot, stir and smelt for 30-60 minutes to obtain the alloy melt; S2. Composite refining and purification: The alloy melt obtained in step S1 is heated to 760-800℃, and high-purity argon and refining agent are introduced by rotary jetting to degas and refine the alloy. The refining time is 15-30 minutes. After refining, the melt is allowed to stand for 10-20 minutes and the slag is removed. S3. Online grain refinement and casting: Adjust the temperature of the melt purified in step S2 to 700-730℃, add Al-5Ti-1B grain refiner online, and then perform semi-continuous casting after filtration through a ceramic filter plate. S4. Two-stage homogenization treatment: The ingot obtained in step S3 is subjected to two-stage homogenization treatment. The first stage is held at 420-450℃ for 6-12 hours, and the second stage is held at 530-560℃ for 12-24 hours. S5. Hot rolling: Heat the ingot after homogenization treatment in step S4 to 480-520℃, hold for 2-4 hours and then hot roll it. The final rolling temperature is controlled at 300-350℃. S6. Intermediate annealing: The hot-rolled strip coil obtained in step S5 is subjected to intermediate annealing under a protective atmosphere. The annealing temperature is 350-420℃ and the holding time is 2-6 hours. S7. Cold rolling and graded aging: The strip annealed in step S6 is subjected to multiple passes of gradient rolling, including roughing, intermediate rolling and finishing rolling, with a total cold rolling deformation of 70-95%, to produce aluminum foil with a thickness of 0.05-0.20 mm; after cold rolling, graded aging heat treatment is performed, with the first stage held at 80-120℃ for 2-6 hours and the second stage held at 150-190℃ for 4-12 hours; S8. Low-temperature stress relief annealing: The aged aluminum foil is subjected to low-temperature precision annealing at 280-300℃ to eliminate residual rolling stress; S9. Precision surface modification: After polishing and cleaning, the annealed aluminum foil is subjected to micro-arc oxidation passivation treatment to obtain the finished aluminum alloy foil.

6. The method for preparing an aluminum alloy for an impact-resistant and explosion-proof film according to claim 5, characterized in that: The refining agent in S2 consists of the following components by mass percentage composition: NaCl: 40~50%, KCl: 30~40%, Na3AlF6: 10~20%, Na2B4O7: 2~8%.

7. The method for preparing an aluminum alloy for an impact-resistant and explosion-proof film according to claim 5, characterized in that: The purity of the high-purity argon gas in S2 is ≥99.99%, the gas flow rate is 2-5 L / min, and the amount of refining agent added is 0.1-0.3% of the melt mass.

8. The method for preparing an aluminum alloy for an impact-resistant and explosion-proof film according to claim 5, characterized in that: In the two-stage homogenization process in S4, the first stage temperature is 435-445℃ for 8-10 hours, and the second stage temperature is 540-550℃ for 16-20 hours.

9. The method for preparing an aluminum alloy for an impact-resistant and explosion-proof film according to claim 5, characterized in that: During the cold rolling process in S7, when the cumulative deformation reaches 50-70%, an intermediate annealing is performed at a temperature of 250-320°C for 1-3 hours.

10. The method for preparing an aluminum alloy for an impact-resistant and explosion-proof film according to claim 5, characterized in that: In the graded aging heat treatment in S7, the heating rate is 20-50℃ / hour.